Meningkatkan Usaha Mikro Kecil Dan Menengah (UMKM) Dengan Program Pasar Minggu - Buchori Muslim, Ahmad; Juniarti, Ervia; Alfiah Misbah, Wanda; Ilham Ramdani, Muhamad (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Banyuwangi, 2024)
Micro, Small and Medium Enterprises activities or what are known as MSMEs contribute to the Indonesian economy. The contribution of MSMEs to the Indonesian economy is equal distribution of income, reducing unemployment and rural economic development. The problem that occurs is the lack of product innovation and people's purchasing power. This activity was carried out with the aim of pioneering the creation of a Sunday market which is expected to improve the community's economy. This activity was carried out at Kp. Cakung, Babat Village, Legok District, Tangerang Regency. The method used in this activity is direct assistance, namely accompanying and providing a place for people who want to become entrepreneurs. Overall, this activity produced results in the form of community enthusiasm for entrepreneurship and increased purchasing power of the local community. The activities that have been carried out provide benefits to the village community, namely that apart from being a place to sell, the Sunday market is used as a means of socializing between residents